Cancer stem cells: The potential role of autophagy, proteolysis, and cathepsins in glioblastoma stem cells - Joachim Bischof; Mike-Andrew Westhoff; Johanna Elisabeth Wagner; Marc-Eric Halatsch; Stephanie Trentmann; Uwe Knippschild; Christian Rainer Wirtz; Timo Burster (Tumor Biology)
One major obstacle in cancer therapy is chemoresistance leading to tumor recurrence and metastasis. Cancer stem cells, in particular glioblastoma stem cells, are highly resistant to chemotherapy, radiation, and immune recognition. In case of immune recognition, several survival mechanisms including, regulation of autophagy, proteases, and cell surface major histocompatibility complex class I molecules, are found in glioblastoma stem cells. In different pathways, cathepsins play a crucial role in processing functional proteins that are necessary for several processes and proper cell function. Consequently, strategies targeting these pathways in glioblastoma stem cells are promising approaches to interfere with tumor cell survival and will be discussed in this review.